Characterization of typical aquatic humic substances in areas of sugarcane cultivation in Brazil using tetramethylammonium hydroxide thermochemolysis - Tadini, A. M. [UNESP]; Constantino, I. C. [UNESP]; Nuzzo, A.; Spaccini, R.; Piccolo, A.; Moreira, A. B. [UNESP]; Bisinoti, M. C. [UNESP] (Elsevier B.V., 2015)
Aquatic humic substances (AHSs) differ from one environment to another depending on land use and occupation. In addition, the effects of planting sugarcane on AHSs are not well known. Thus, the aim of this study was to characterize AHSs extracted from a river in a typical region of sugarcane cultivation during dry and rainy seasons. The main characteristics of the AHSs were obtained using Fourier transformation infrared (FTIR) spectroscopy, nuclear magnetic resonance (NMR) spectroscopy and off-line pyrolysis coupled with gas chromatography and mass spectrometry (off-line tetramethylammonium hydroxide (TMAH)-GC-MS-thermochemolysis). The FTIR and NMR results were used to infer that no distinctions occurred between the sampling periods. The samples were composed of aromatic groups that were potentially associated with the presence of residual vegetable materials (lignin). The results of the off-line TMAH-GC-MS-thermochemolysis indicated that the structures of the AHSs had uniform compositions that were rich in fatty acid methyl esters (FAMEs), polysaccharide derivatives, aliphatic biopolymers derived from plants, long hydrocarbon chains, branched alkyl groups and methylene carbons. Thus, the results showed that the AHSs obtained from the sugarcane cultivation area during the crop period mainly consisted of resistant aliphatic hydrocarbons, which are derivatives of lignin and FAMEs in compounds rich in humic acid. Therefore, we concluded that sugarcane cultivation produces changes in AHSs because greater amounts of lignin derivatives were observed during the dry season, corresponding to sugarcane cultivation. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Aquatic humic substances; NMR; Infrared; Off-line TMAH-GC-MS; Sugarcane